Concentration and Foreign Penetration in Latin American Banking Sectors: Impact on Competition and Risk - Eduardo Levy Yeyati; Alejandro Micco (Inter-American Development Bank, Research Department, 2003)
In recent years, Latin American banking sectors have experienced an accelerated process of concentration and foreign penetration that has prompted diverse views regarding its implications for the competitive behavior of banks and for the financial stability of the system as a whole. Exploiting a rich bank-level balance sheet database for eight Latin American countries, we examine the evolution of concentration and foreign penetration indicators and their impact on competition and risk. We find that, while concentration did not reduce competition in the industry, foreign penetration appears to have led to less competitive banking sectors. Moreover, we find banking sector fragility to be positively related to competition and, through this channel, negatively related to foreign participation, despite the fact that foreign banks in the region are associated with higher insolvency risk due to higher leverage ratios and more volatile returns.
Keywords: 330; Bank; Unternehmenskonzentration; Internationale Bank; Wettbewerb; Lateinamerika